The performance of energy absorption in structural profiles with different discontinuities. Issue 5 (May 2016) - Estrada, Quirino; Szwedowicz, Dariusz; Baltazar, Martin; Cortes, Claudia; Majewski, Tadeusz; Estrada, Claudio
Abstract A numerical study of the energy absorption characteristics of structural steel is presented, by implementing geometric imperfections. The geometric discontinuities were placed at half height of the structures in two opposite walls. In this case, different curved shapes discontinuities and quadrilaterals were evaluated. The shape and aspect ratio of the discontinuity modify the behavior of the structure even though the analyzed shapes have the same area value. The best performance in energy absorption of 12.54 % compared to a shape with no discontinuities was obtained with the implementation of a curved form initiator. Finally, and with the same comparison pattern, the value of the peak load was reduced up to 22.13 % by using the diamond-shaped discontinuities.